Persepsi Konsumen terhadap Rumah Makan Cepat Saji - Rikie Dekas (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the analysis of consumer perceptions of Ayam Geprek Sambal Petir (Survey on Consumers of Chicken Geprek Sambal Petir Restaurant Prabumullih Branch). The method in this research is a quantitative research method. Quantitative methods were used to determine the level of increase in the number of visitors to the Geprek Sambal Petir Chicken in Prabumulih City. This study uses a sampling technique with the respondents are the customers of Ayam Geprek Sambal Petir. Data analysis was carried out using a Likert scale developed from a questionnaire. The results showed that the development of Chicken Geprek Sambal Petir in Prabumulih City is currently growing very rapidly. The manager of the Geprek Sambal Petir continues to maintain its trademark of being one of the favorite foods for young people. To maintain good quality, the manager continues to innovate such as maintaining price quality, taste, lifestyle, and interior design. Basically, so that customers remain loyal and the Chicken Geprek Sambal Petir remains excellent in the eyes of the people of Prabumulih City. In conclusion, good management of the Geprek Sambal Lightning Chicken will also bring goodness. In the midst of competition from culinary traders in Prabumulih City, the manager of Ayam Geprek Sambal Petir continues to innovate and continues to try to promote to the public so that they can become loyal customers. Keywords: Analysis, Chicken Geprek Sambal Lightning, Prabumulih